The Effectiveness of the Unified Agro-industrial Policy of the EAEU Is the Key to Success - A. I. Ageev; O. A. Zolotareva (Евразийская интеграция: экономика, право, политика)
The increasing intensity of the sanctions pressure of Western countries on the Russian Federation as a locomotive ensuring the economic growth of the EAEU, as well as on the Republic of Belarus, the prospects of falling under secondary sanctions of other member countries of the Union, are inevitably reflected in the physical and economic availability of food both in each of the EAEU member countries and in the Union as a whole. The new situation requires an objective analysis of the potential for ensuring food security.Aim and tasks. To characterize the state and dynamics of agricultural production in the context of achieving food security of the EAEU member states for the period from 2014 to 2023.Methods. Based on official statistics from the Department of Statistics of the Eurasian Economic Commission, the Interstate Statistical Committee of the CIS and the national statistical committees of the EAEU member states, comparative analytics and descriptive statistics were used to assess the current state and analyze trends in agricultural production in the EAEU.Results. It has been revealed that the risks of food security in each of the EAEU member states are significantly reduced in the integration space, which is primarily facilitated by mutual provision of certain food products. At the same time, the determinant of food security of the EAEU is undoubtedly the sustainable development of agriculture, which has ensured the growth of physical availability of food products in the Union countries. Self-sufficiency in basic agricultural products at the Union level is assessed as high. However, a number of Union member countries have recorded risks for self-sufficiency in certain products of their own production, associated with possible interruptions in imports in the event of unforeseen situations.Conclusions. The risks associated with global food security are growing significantly in the world. The value of food resources, which some experts recognize as the “new oil”, is increasing [2]. Productive and stable growing agriculture in the EAEU is not only the basis for ensuring food security, but also the driver of sustainable macroeconomic development of both the Union as a whole and the EAEU member states.